Using immunoglobulin Y as an alternative antibody for the detection of hepatitis A virus in frozen liver sections - Gentil Arthur Bentes; Natália Maria Lanzarini; Lyana Rodrigues Pinto Lima; Pedro Paulo de Abreu Manso; Alexandre dos Santos da Silva; Sergio da Silva e Mouta Junior; Juliana Rodrigues Guimarães; Marcia Terezinha Baroni de Moraes; Marcelo Pelajo-Machado; Marcelo Alves Pinto (Memorias do Instituto Oswaldo Cruz, 2015)
An increasing amount of research has been conducted on immunoglobulin Y (IgY) because the use of IgY offers several advantages with respect to diagnostic testing, including its easy accessibility, low cost and translatability to large-scale production, in addition to the fact that it can be ethically produced. In a previous work, immunoglobulin was produced and purified from egg yolks (IgY) reactive to hepatitis A virus (HAV) antigens. In the present work, this anti-HAV-specific IgY was used in an indirect immunofluorescence assay to detect viral antigens in liver biopsies that were obtained from experimentally infected cynomolgus monkeys. Fields that were positive for HAV antigen were detected in liver sections using confocal microscopy. In conclusion, egg yolks from immunised hens may be a reliable source for antibody production, which can be employed for immunological studies.